TRPV4 Is Required for Hypoxic Pulmonary Vasoconstriction. (June 2015) - Goldenberg, Neil M.; Wang, Liming; Ranke, Hannes; Liedtke, Wolfgang; Tabuchi, Arata; Kuebler, Wolfgang M.
<x xml:space="preserve">Abstract</x> Background: Hypoxic pulmonary vasoconstriction (HPV) is critically important in regionally heterogeneous lung diseases by directing blood toward better-oxygenated lung units, yet the molecular mechanism of HPV remains unknown. Transient receptor potential (TRP) channels are a large cation channel family that has been implicated in HPV, specifically in the pulmonary artery smooth muscle cell (PASMC) Ca2+ and contractile response to hypoxia. In this study, the authors probed the role of the TRP family member, TRPV4, in HPV. Methods: HPV was assessed by using isolated perfused mouse lungs or by intravital microscopy to directly visualize pulmonary arterioles in mice. In vitro experiments were performed in primary human PASMC. Results: The hypoxia-induced pulmonary artery pressure increase seen in wild-type mice (5.6 ± 0.6 mmHg; mean ± SEM) was attenuated both by inhibition of TRPV4 (2.8 ± 0.5 mmHg), or in lungs from TRPV4-deficient mice (Trpv4−/−) (3.4 ± 0.5 mmHg; n = 7 each). Functionally, Trpv4−/− mice displayed an exaggerated hypoxemia after regional airway occlusion (paO2 71% of baseline ± 2 vs. 85 ± 2%; n = 5). Direct visualization of pulmonary arterioles by intravital microscopy revealed a 66% reduction in HPV in Trpv4−/− mice. In human PASMC, inhibition of TRPV4 blocked the hypoxia-induced Ca2+ influx and myosin light chain phosphorylation. TRPV4 may form a heteromeric channel with TRPC6 as the two channels coimmunoprecipitate from PASMC and as there is no additive effect of TRPC and TRPV4 inhibition on Ca2+ influx in response to the agonist, 11, 12-epoxyeicosatrienoic acid. Conclusion: TRPV4 plays a critical role in HPV, potentially via cooperation with TRPC6.